Improved rate capability and cycling stability of novel terbium-doped lithium titanate for lithium-ion batteries. (20th August 2016) - Zhang, Ping; Huang, Yudai; Jia, Wei; Cai, Yanjun; Wang, Xingchao; Guo, Yong; Jia, Dianzeng; Sun, Zhipeng; Guo, Zaiping
Abstract: Li4 Ti4.94 Tb0.06 O12-δ has been synthesized via a facile co-precipitation method. The structure and morphology of the as-prepared sample have been characterized by X-ray diffraction, X-ray photoelectron spectroscopy, scanning electron microscopy, and particle size distribution analysis. The results show that Tb 3+ is successfully doped into the Li4 Ti5 O12 structure and that the average particle size is about 111 nm. Li4 Ti4.94 Tb0.06 O12-δ exhibits a high initial discharge capacity of 166.5 mAh g −1 at 20 C, and the discharge capacity retention is nearly 93% after 500 cycles. In addition, the sample shows much improved rate capability at 20 C compared with pure Li4 Ti5 O12 . Tb 3+ doping not only enhances the electronic conductivity, but also improves the Li + ion diffusivity in Li4 Ti5 O12, which indicates that Tb 3+ doping is beneficial for promoting the electrochemical performance of Li4 Ti5 O12 .